How to advance from minimally invasive coronary artery bypass grafting to totally endoscopic coronary bypass grafting: challenges in Europe versus United States of America - Algoet, Michiel; Melvin, Tom; Cerny, Stepan; Bonatti, Johannes; Singh, Sandeep; Folliguet, Thierry; Modi, Paul; Franke, Ulrich; Gianoli, Monica; Agnino, Alfonso; Casselman, Filip; Oosterlinck, Wouter (Annals of cardiothoracic surgery, 2024)
Robotic coronary and intra-cardiac surgery has been available for more than 25 years. In this period, multiple studies have demonstrated the beneficial effects of robotic surgery over conventional open surgery. Throughout the years, technical developments have enabled us to perform totally endoscopic coronary artery bypass (TECAB) grafting. But these techniques remained in the hands of a small group of pioneers because of a lack of structured training programs and the absence of long-term results at that time. Currently, a renewed interest and a wide dispersion of robotic platforms, thanks to use of robotics in other disciplines, has led to an exponential increase in robotic cardiac centers both in Europe and USA. Nonetheless, this increase was slowed down in Europe as a result of the uncertainty introduced by the implementation of a revised regulatory framework for medical devices [Regulation 2017/745, 'Medical Device Regulation' ('MDR')]. The MDR was introduced with the goal of increasing patient safety and supporting innovation. Implementing the MDR has proven to be exceptionally challenging and risks to the supply of essential devices have been identified. Changes to both regulatory and market dynamics led to a circumstance where the only available robotic platform for cardiac surgery decided to cease marketing of essential accessories for conducting surgery. This resulted in the disappearance of dedicated tools such as the Endowrist stabilizer, essential for TECAB, and the atrial retractor which is essential for intra-cardiac surgery. In the mean-time, further clinical evidence was published demonstrating the superiority of robotic cardiac surgery over other minimally invasive approaches. This has demonstrated the need to better define the clinical evidence requirements for regulatory purposes to ensure that dedicated tools for evidence-based interventions in robotic coronary surgery remain available such that TECAB can continue in Europe.
Keywords: Totally endoscopic coronary artery bypass (TECAB); robotic cardiac surgery; minimally invasive direct coronary artery bypass (MIDCAB)